The T-type calcium channelosome - Weiss, Norbert; Zamponi, Gerald W (Pflugers Archiv, 2024)
T-type calcium channels perform crucial physiological roles across a wide spectrum of tissues, spanning both neuronal and non-neuronal system. For instance, they serve as pivotal regulators of neuronal excitability, contribute to cardiac pacemaking, and mediate the secretion of hormones. These functions significantly hinge upon the intricate interplay of T-type channels with interacting proteins that modulate their expression and function at the plasma membrane. In this review, we offer a panoramic exploration of the current knowledge surrounding these T-type channel interactors, and spotlight certain aspects of their potential for drug-based therapeutic intervention.
Keywords: Calcium; vápník; Calcium channels; T-type channels; Calcium Channel Blockers; Calcium Channels, T-Type; blokátory kalciových kanálů; vápníkové kanály - typ T; Ion channels; neurony; Channelosome; Neurons